Agricultural policy of the Russian Federation - Sklyarov, Igor; Sklyarova, Yuliya (Economics of Agriculture, 2010)
State support for the agricultural sector is an important national economic problem, since agriculture is one of the sectors, which has traditionally built the entire Russian economy, and this machinery, the consumption of petroleum products (diesel fuel), transportation, storage, processing, etc.